Synthesis and determination of the Sun Protection Factor of a cosmetic gel-cream based on norbixin - Garcia, Simey do Vale; Alves, Patrícia e Silva; Dias, Leandro de Sousa; Santos, Leandro Josuel da Costa; Lustosa, Sérgio Marcelo Coelho; Viana, Deuzuíta dos Santos Freitas; Viana, Vicente Galber Freitas (Seven Editora, 2023)
This work aimed to determine the Sun Protection Factor (SPF) of a cream-gel based on norbixin through spectrophotometry. Samples of gel-cream A and B were prepared at a concentration of 0.2 μL/mL and the absorbances were measured in the UVB region and the SPF was calculated using the equation used in the Mansur method. The absorption spectrum of each cream-gel was obtained using the origin program. Gel-creams A and B showed absorption in the UVA and UVB region and also in the long UVA region, therefore, they presented photoprotective characteristics. Regarding the Sun Protection Factor - SPF, both the cream-gel A and the cream-gel B were considered photoprotective by ANVISA. Norbixin increased the Sun Protection Factor - SPF and this potentiation was proportional to its concentration. Therefore, the use of norbixin in photoprotective products proved to be effective, favoring an increase in the photoprotection of the formulations.DOI:https://doi.org/10.56238/globalhealthprespesc-069